The genus Ramalina Acharius (Ascomycota, Lecanoromycetes, Ramalinaceae) in northern South America - Marcano, Vicente; Méndez, Antonio Morales; Prü, Ernesto Palacios (Phytotaxa, 2021)
Fifty three taxa of Ramalina Acharius have been found in northern South America (including Colombia and Venezuela), with 8 varieties and 48 species. Seven species and four varieties are described as new to science viz. R. anteojina V. Marcano & A. Morales sp. nov. (Venezuela), R. canaguensis V. Marcano & A. Morales var. colombiana Marcano & Morales var. nov. (Colombia), R. canaguensis Marcano & Morales var. guascasensis Marcano & Morales var. nov. (Colombia), R. canaguensis V. Marcano & A. Morales var. mucumpisensis V. Marcano & A. Morales var. nov. (Colombia and Venezuela), R. reducta Krog & Swinscow var. colombiana V. Marcano & A. Morales var. nov. (Colombia), R. maegdefraui  V. Marcano & A. Morales sp. nov. (Venezuela), R. mirandensis V. Marcano & A. Morales sp. nov. (Venezuela), R. subcalcarata V. Marcano & A. Morales sp. nov. (Venezuela), R. tenaensis V, Marcano & Morales sp. nov. (Colombia), R. venezuelensis V. Marcano & A. Morales sp. nov. (Venezuela), and R. victoriana V. Marcano & L. Castillo sp. nov. (Venezuela); 8 taxa are reported for first time from Venezuela: R. anceps Nylander, R. bogotensis Nylander, R. chilensis Bertero, R. holstii Krog & Swinscow, R. rigida Persoon ex Acharius, R. sorediosa (Bouly de Lesdain) Landrón, R. subfraxinea Nylander var. subfraxinea, and R. tenella Müller Argoviensis, whereas 5 taxa are reported for the first time from Colombia: R. africana (Stein) Dodge, R. asahinae W. Culberson & C. Culberson, R. subfraxinea Nylander var. confirmata, R. tenuissima V. Marcano & A. Morales and R. vareschii V. Marcano & A. Morales. A key to the species is presented together with data on morphology, anatomy, chemistry, variation, taxonomy, habitat and distribution. The chemical analyses show that the sekikaic (24 taxa), boninic (16 taxa) and homosekikaic (15 taxa) acids are the most common depsides found. Divaricatic acid is present in 10 of the taxa but is frequently replaced by sekikaic acid and its aggregates. The most common depsidones are salazinic acid (22 taxa), and protocetraric acid (25 taxa). The distribution of the secondary compounds reveals they are able to produce quite different substances which appears be not dependent to the habitat where occur the species, neither to the occurrence of minute morphological or anatomical differences at similar species. Often, several chemical strains (chemosyndromes) can be recognized within a single population of a particular species, but have no correlation with morphology or ecology. Biogeographic data indicate that of the 53 taxa known from northern South America, 28.3% (15) are known only from Venezuela, 7.5% (4) are known only from Colombia and 18.9% (10) are known only from Venezuela and Colombia. Of the 50 taxa known from Venezuela, 70% (37) of the taxa have their main distribution in the Andean region. The high concentration of Ramalina species seen in the Andes indicates that this region constitutes an important centre for speciation and endemism of Ramalina both in northern South America but also throughout the world.